Perfect competition and monopoly - Ramesh, Sangaralingam (Henry Stewart Talks, 2019)
Market structures, Perfect competition, Monopolies, Local monopoly, Regulated monopoly, Barriers to market entry, Price makers & price takers, Supernormal profits, Monopolists’ revenues and elasticity